Sustainable Rainwater Management through Green Infrastructure: A Rain Garden Project in Dharma Wanita Caruban Kindergarten, Bojonegoro - Yuliani Wahyu Sardana; Yulia Indriani; Bagas Pramudya Yudistira; Jaka Setiana (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to implement a Rain Garden as a solution for water retention and infiltration while serving as a living laboratory for the cultivation of water conservation awareness within the school community. The implementation method of this community service activity uses a design and build approach through the engagement of stakeholders, following the systematic stages of Planning, Action, Observation, and Reflection (PAOR). The construction of a filtration layering structure utilized a calculated mixture of sand, compost, and local soil (5:2:3 ratio) over a 9.9 m² managed area with an excavation depth of 1.2 meters. The partners involved are the school community at Dharma Wanita Caruban Kindergarten, Bojonegoro. The evaluation instruments used in this activity were hydrological performance observations of infiltration rates and retention capacity, supplemented by Likert-scale structured observation sheets to measure partner competence. The data were analyzed using the descriptive-comparative technique. The results of this community service program indicate that the implemented system, with its calculated retention capacity, facilitates total rainwater infiltration within a 24-hour period, effectively eliminating surface ponding. Beyond hydrological performance, the project achieved a substantial average increase of 55% in partner competence, reaching a final proficiency level of 90%. The design successfully transforms passive land into a functional garden with adaptive vegetation for the maintenance of optimal soil porosity. This established Rain Garden provides a sustainable water conservation model and serves as an ecological educational instrument for students in Bojonegoro.